2020
DOI: 10.1016/j.jaac.2020.05.009
|View full text |Cite
|
Sign up to set email alerts
|

Rapid Systematic Review: The Impact of Social Isolation and Loneliness on the Mental Health of Children and Adolescents in the Context of COVID-19

Abstract: Objective: Disease containment of COVID-19 has necessitated widespread social isolation. We aimed to establish what is known about how loneliness and disease containment measures impact on the mental health in children and adolescents. Method: For this rapid review, we searched MEDLINE, PsycInfo, and Web of Science for articles published between January 1, 1946, and March 29, 2020. Of the articles, 20% were double screened using predefined criteria, and 20% of data was double extracted for quality assurance. R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

91
1,920
5
105

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 2,158 publications
(2,121 citation statements)
references
References 81 publications
91
1,920
5
105
Order By: Relevance
“…Government measures put in place to contain the virus have physically and socially isolated adolescents from their friends, extended family, and other social support networks, leaving many feeling socially isolated, and consequently, at an increased risk of psychological disorder. However, to date, there has been no longitudinal research examining how the pandemic has impacted adolescents’ mental health despite decades of research demonstrating the potential lifelong risks associated with prolonged interpersonal stress and social isolation during the adolescent years (e.g., Loades et al 2020 ). Further, research has not yet examined which demographic and COVID-19 related factors serve to increase or decrease adolescent mental health symptoms over time.…”
Section: Discussionmentioning
confidence: 99%
“…Government measures put in place to contain the virus have physically and socially isolated adolescents from their friends, extended family, and other social support networks, leaving many feeling socially isolated, and consequently, at an increased risk of psychological disorder. However, to date, there has been no longitudinal research examining how the pandemic has impacted adolescents’ mental health despite decades of research demonstrating the potential lifelong risks associated with prolonged interpersonal stress and social isolation during the adolescent years (e.g., Loades et al 2020 ). Further, research has not yet examined which demographic and COVID-19 related factors serve to increase or decrease adolescent mental health symptoms over time.…”
Section: Discussionmentioning
confidence: 99%
“…In the face of the COVID-19 pandemic, many scholars have turned to considering the impact that the pandemic has on children's and adolescents' mental health. Particularly, prior research has shown that social isolation is associated with increased rates of depression in children and adolescents (Loades et al, 2020). To date, however, most of the recent scholarship has been either commentary aimed at policy or practice or research (Wang et al, 2020;Liu et al, 2020;Power et al, 2020;Ghosh, Dubey, Chatterjee, & Dubey, 2020;Golberstein, Wen, & Miller, 2020;Mahajan, Kapoor, & Prabhakar, 2020), or cross-sectional empirical studies (see Pisano, Galimi, & Carniglia, Preprint, April 13 2020) (Xie et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Evidence has identi ed loneliness as a strong precursor of stress, depression, anxiety, and suicide, which could potentially exacerbate pre-existing psychological and mental issues (Holmes et al, 2020;Lim et al, 2020). Recent studies have shown that social isolation and loneliness due to home con nement measure increase the risk of psychological distress, depression, and anxiety in an individual, with a longer duration of loneliness considered as a strong precursor of adverse psychiatric symptoms (Rauschenberg et al, 2020;Loades et al, 2020). Further, other reports have strongly linked loneliness to various diseases such as stroke, hypertension, and other heart issues, as well as other cognitive issues such as dementia (Valtorta et al, 2016;Kuiper et al, 2015).…”
Section: Introductionmentioning
confidence: 99%